Interleukin‐1βconverting enzyme: A novel cysteine protease required for IL‐1β production and implicated in programmed cell death - Thornberry, Nancy A.; Molineaux, Susan M. (Protein science, 1995)
Interleukin‐1β converting enzyme is the first member of a new class of cysteine proteases. The most distinguishing feature of this family is a nearly absolute specificity for cleavage at aspartic acid. This enzyme has been the subject of intense research because of its role in the production of IL‐1β, a key mediator of inflammation. These studies have culminated in the design of potent inhibitors and determination of its crystal structure. The structure secures the relationship of the enzyme to CED‐3, the product of a gene required for programmed cell death in Caenorhabditis elegans, suggesting that members of this family function in cell death in vertebrates.